The Supernatural in Ideology of Ancestral Society - Gendrolis, Edmundas (Problemos, 1981)
Syncretism in ideology of ancestral society does not give sufficient reason to be counted as religious ideology, which is sought to be proved by representatives of idealistic social methodology. Contradiction between knowledge and faith, reality and fantasy, is not found to be explicitly expressed in mythology, fantasy being predominant in the case where practical experience, positive knowledge, becomes exhausted. Specific character of the supernatural in the above ideology lies in the fact it does not contradict the natural, meanwhile it is not entirely identical.